Multiple hypercementosis – a case report of an incidental finding on panoramic radiograph - Ichda Nabiela Amiria Asykarie; Fahri Reza Ramadhan; Ria Noerianingsih Firman (Jurnal Radiologi Dentomaksilofasial Indonesia (JRDI), 2022)
Objectives: This case report is aimed to describe radiographic features of multiple hypercementosis in an incidental case. Case Report: A 38-year-old man came to the Dental Hospital of Padjadjaran University with a complaint that he had lost some of his teeth and wanted to make dentures because he found it difficult to chew food. Then the patient was referred for a radiographic examination, the results of a panoramic radiograph found abnormalities in the form of thickening of the cementum at the apex of the remaining teeth. The teeth were in vital condition and there were no clinical signs. Conclusion: Based on the examination results, it was concluded that the panoramic radiograph showed excessive cementum thickening and root enlargement on the remaining teeth. This case leads to a radiological diagnosis suspect of multiple hypercementosis or cementum hyperplasia.